Crystal structure of catena-poly[(5,5,7,12,12,14-hexamethyl -1,4,8,11-tetraazacyclotetradecane- κ4N,N′,Nʺ,N‴)nickel(II)-(μ2-perchlorato-κ2O:O′)] 3,5-dicarboxybenzoate – methanol (1/2), C27H49ClN4NiO12 - Wang Qiong; Ou Guang-Chuan (Zeitschrift für Kristallographie - New Crystal Structures)
C27H49ClN4NiO12, triclinic, P1‾$\overline{1}$ (no. 2), a = 11.180(2) Å, b = 12.320(3) Å, c = 12.754(3) Å, α = 98.263(2)°, β = 97.524(2)°, γ = 99.470(2)°, V = 1693.1(6) Å3, Z = 2, Rgt(F) = 0.0423, wRref(F2) = 0.1238, T = 296(2) K.